Філософські принципи у праві - Сливка, С. (Видавництво Львівської політехніки, 2014)
Досліджено принципи філософії права, виділено принципи буття та принципи пізнання, на основі яких аналізуються онтологічні та гносеологічні принципи філософії права, доведена динамічна єдність цих принципів. In the article the principles of philosophy of law are analyzed. It is emphasized the principles of objective reality and cognition on the basis of which ontological and epistemological principles of legal philosophy are analyzed. The dynamic unanimity of these principles is proved. Исследуются принципы философии права, выделяются принципы бытия и принципы познания, на основе которых анализируются онтологичнеские и гносеологические принципы философии права, доказывается динамичное единство этих принципов.
Philosophical principles of law
Keywords: принципи буття; принципи пізнання; принципи права; принципи філософії права; Principles of objective reality; principles of cognition; principles of law; principles of legal philosophy; принципы бытия; принципы познания; принципы права; принципы философии права